2014
DOI: 10.1016/j.jvs.2013.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Dual antiplatelet therapy (clopidogrel and aspirin) is associated with increased all-cause mortality after carotid revascularization for asymptomatic carotid disease

Abstract: In this retrospective, single-institution study, the use of dual antiplatelet therapy (aspirin plus clopidogrel) in patients intervened for asymptomatic carotid disease was related to increased all-cause mortality, whereas it did not significantly influence the outcome in patients with symptomatic carotid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…If clopidogrel is initiated at the time of CEA, there is currently no evidence establishing the duration of therapy. Alcocer et al 20 reported that patients on dual therapy after CEA for asymptomatic disease demonstrated higher rates of all-cause mortality over a median follow-up of >4 years, suggesting that the risks of dual antiplatelet therapy may extend beyond the perioperative beneficial effects observed in this report.…”
Section: Discussionmentioning
confidence: 60%
“…If clopidogrel is initiated at the time of CEA, there is currently no evidence establishing the duration of therapy. Alcocer et al 20 reported that patients on dual therapy after CEA for asymptomatic disease demonstrated higher rates of all-cause mortality over a median follow-up of >4 years, suggesting that the risks of dual antiplatelet therapy may extend beyond the perioperative beneficial effects observed in this report.…”
Section: Discussionmentioning
confidence: 60%
“…10,11 On the contrary, other studies demonstrated an increased mortality or higher bleeding rates for dual antiplatelet therapy. 12,13 In addition, a recent metaanalysis could not demonstrate an advantage of dual antiplatelet therapy over monotherapy in terms of prevention of stroke and death after CEA, but there was an increased risk of bleeding complications. 14 Thus, there is still some uncertainty about the use of dual antiplatelet therapy in the perioperative period of CEA.…”
Section: Date Of Release December 1 2018 Expiration December 31 2019mentioning
confidence: 99%
“…Only two studies investigated the effect of dual versus single antiplatelet therapy in patients with symptomatic and asymptomatic carotid disease undergoing CEA. Alcocer et al 10 demonstrated an increased mortality rate in patients with asymptomatic carotid disease receiving dual antiplatelet therapy as compared with aspirin alone (47% vs. 40%; p ¼ .05). In patients with symptomatic carotid disease, dual antiplatelet therapy was associated with a nonsignificant decrease in all-cause mortality (38% vs. 39%; p ¼ .53).…”
Section: Discussionmentioning
confidence: 98%
“…Although monotherapy (aspirin or clopidogrel) is widely accepted during the perioperative period of carotid intervention for stroke prevention, the role of dual antiplatelet therapy (aspirin and clopidogrel), which has a pivotal role in coronary artery disease (CAD), is less clear. 10 The objective was to undertake a comprehensive literature review and perform a meta-analysis to assess the effects of dual antiplatelet therapy in carotid interventions.…”
Section: Introductionmentioning
confidence: 99%